Security Convergence In Southeast Asia: Indonesia's Initiative In Asean Our Eyes (AOE) 2017 - Khoirunnisa; Nabila, Firdiyatul; Roza (Yayasan Ilomata, 2024)
Security convergence in the Southeast Asian region has become an important focus, particularly with Indonesia's initiative in ASEAN Our Eyes (AOE) in 2017. In this regard, the purpose of this research is to identify Indonesia's interest in initiating ASEAN Our Eyes (AOE) as a strategic step in enhancing regional security in the Southeast Asian Region and highlight the importance of intelligence cooperation in the context of cyber defence as well as add to the understanding of new strategies to enhance regional security stability in the Southeast Asian Region. The support for this initiative was triggered by a series of terrorism and cyber events in the region, including bomb attacks and global malware such as WannaCry and Fireball in the same year. In this study, a qualitative approach with a literature study technique was used to identify Indonesia's interest in the AOE and its impact on regional security. The results show that through regional intelligence cooperation, Indonesia can access crucial information to counter threats, as well as strengthen its domestic intelligence capacity. Furthermore, the exchange of information and best practices in intelligence is expected to enhance Indonesia's ability to detect, prevent, and respond to security threats. Thus, Indonesia's participation in the AOE is not only in its national interest, but also to support regional security stability in Southeast Asia. This highlights the importance of cyber diplomacy and intelligence collaboration in dealing with modern security challenges.